2022
DOI: 10.3390/ma15176154
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compressive Mechanical Properties of UR50 Ultra-Early-Strength Cement-Based Concrete Material under High Strain Rate on SHPB Test

Abstract: UR50 ultra-early-strength cement-based self-compacting high-strength material is a special cement-based material. Compared with traditional high-strength concrete, its ultra-high strength, ultra-high toughness, ultra-impact resistance, and ultra-high durability have received great attention in the field of protection engineering, but the dynamic mechanical properties of impact compression at high strain rates are not well known, and the dynamic compressive properties of materials are the basis for related nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Based on the above analysis and combined with the results shown in Table 9 , it was found that with the increase in the strain rate, parameter increased, and the rate of damage evolution of the PFRC decreased. Several scholars have found that the damage evolution rate of basalt fiber concrete, polypropylene fiber concrete and ultra-early strength concrete also decreases with an increasing strain rate [ 6 , 35 , 49 ]. The reason for this phenomenon may be that at high strain rates, the cracks inside the PFRC do not have enough time to expand, resulting in a reduced rate of their damage evolution.…”
Section: Dynamic Constitutive Model Of Pfrcmentioning
confidence: 99%
“…Based on the above analysis and combined with the results shown in Table 9 , it was found that with the increase in the strain rate, parameter increased, and the rate of damage evolution of the PFRC decreased. Several scholars have found that the damage evolution rate of basalt fiber concrete, polypropylene fiber concrete and ultra-early strength concrete also decreases with an increasing strain rate [ 6 , 35 , 49 ]. The reason for this phenomenon may be that at high strain rates, the cracks inside the PFRC do not have enough time to expand, resulting in a reduced rate of their damage evolution.…”
Section: Dynamic Constitutive Model Of Pfrcmentioning
confidence: 99%
“…This concrete is characterized by ultra-high strength, ultra-high toughness, ultra-impact resistance, and ultra-high durability. Wei et al [ 27 , 28 ] also researched the mechanical properties and penetration resistance of this high-density concrete. The density of foamed concrete was relatively low, and the density span was large, ranging from 300 kg/m³ to 1600 kg/m³.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete is widely used in civil engineering structures [ 1 , 2 ]. With the rapid development of the economy, many important economic facilities are threatened by accidental explosions and terrorist attacks [ 3 ].…”
Section: Introductionmentioning
confidence: 99%